The effect of the ginger on the apoptosis of hippochampal cells according to the expression of BAX and Cyclin D1 genes and histological characteristics of brain in streptozotocin male diabetic rats - Molahosseini, A.; Taghavi, M. M.; Taghipour, Z.; Shabanizadeh, A.; Fatehi, F.; Kazemi Arababadi, M.; Eftekhar Vaghefe, S. H. (Cellular and Molecular Biology, 2016)
Diabetes is the most common endocrine disorder in humans with multiple complications including nervous system damages. The aim of the present study was to determine the effect of ginger extract on apoptosis of the neurons of hippocampus, via evaluation of BAX and Cyclin D1 and also histological analysis, in male diabetic rats. In this experimental study, 60 Wistar rats (220 ± 30gr) were conducted in 5 groups as follow: diabetic group treated with saline (group 1), normal group treated with saline (group 2), diabetic group treated with ginger (group 3), diabetic group treated with ginger-insulin (group 4), diabetic group treated with insulin (group 5). STZ (60 mg/kg) was intraperitoneally used to induce the diabetes. Expression levels of BAX and Cyclin D1 were examined using Real-Time PCR technique and the normality of neurons was evaluated using H&E staining method. The results showed that blood glucose level significantly decreased in group 4 when compared to group 1. In molecular analysis, there was no significant difference between groups regarding the expression of BAX gens, while, the expression of Cyclin D1 were significantly decreased in group 4 compared with group 1. Histological analysis revealed that pathological symptoms were lower in group 4 than the other diabetic groups. The results of present study showed that the ginger in addition to lowering blood sugar level, changes the expression of Cyclin D1 gene and histological characteristics in a positive manner. This means that the ginger may protects neurons of the hippocampus from apoptosis in diabetic patients.